Vertical migrations in two hygrophilous species of micro‐snails in relation to time of the year and habitat type. Issue 2 (14th June 2019) - Książkiewicz‐Parulska, Zofia
Abstract: The aim of this study was to investigate vertical migration behaviors in two species of hygrophilous micro‐snails, Vertigo moulinsiana and Vertigo angustior, in relation to the time of the year (spring and summer) at two sites that differ in ground water level (periodically inundated site and non‐inundated site). The study shows different patterns of vertical migrations in the studied species. Vertigo angustior demonstrated a strong affinity to the litter layer (a weak tendency for vertical movements), independent of the time of year and site studied. By contrast, V. moulinsiana showed a clear tendency for vertical migrations, which differed depending on the time of year and site. These differences may be related to the spatial segregation of microhabitats used by these two species at the sites studied and to differences in the ability to resist inundation. Vertigo angustior is associated with microhabitats which are not subjected to prolonged inundation and tolerates a brief submersion. The periodic character of vertical migrations may suggest the effect of endogenous factors related to reproduction in V. moulinsiana . Some plasticity of this behavior in relation to habitat conditions demonstrated by this species may be an adaptation to live in unpredictably flooded environments.